2006
DOI: 10.1038/sj.cdd.4402066
|View full text |Cite|
|
Sign up to set email alerts
|

After shrinkage apoptotic cells expose internal membrane-derived epitopes on their plasma membranes

Abstract: Apoptosis and phagocytosis of apoptotic cells are crucial processes. At best the phagocytic machinery detects and swallows all apoptotic cells in a way that progression to secondary necrosis is avoided. Otherwise, inflammation and autoimmune diseases may occur. Most apoptotic cells are phagocytosed instantaneously in a silent fashion; however, some dying cells escape their clearance. If the cells are not cleared early, they lose membranes due to extensive shedding of membrane surrounded vesicles (blebbing) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 30 publications
3
63
0
7
Order By: Relevance
“…Indeed, a substantial fraction of cells responding to chemotherapy in vitro exposed LAMP1 on the cell surface as it externalized PS residues, in line with the hypothesis that lysosomes fuse with the plasma membrane during the apoptotic process. 55 In this setting, the depletion of essential autophagic factors including AT5, ATG7 and BCN1 failed to affect the translocation of LAMP1 to the outer leaflet of the plasma membrane, meaning that autophagy is not required for lysosomal exocytosis. In sharp contrast, the knockdown of PANX1 prevented LAMP1 from translocating to the plasma membrane, and vice versa LAMP1 depletion interfered with the externalization of PANX1.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, a substantial fraction of cells responding to chemotherapy in vitro exposed LAMP1 on the cell surface as it externalized PS residues, in line with the hypothesis that lysosomes fuse with the plasma membrane during the apoptotic process. 55 In this setting, the depletion of essential autophagic factors including AT5, ATG7 and BCN1 failed to affect the translocation of LAMP1 to the outer leaflet of the plasma membrane, meaning that autophagy is not required for lysosomal exocytosis. In sharp contrast, the knockdown of PANX1 prevented LAMP1 from translocating to the plasma membrane, and vice versa LAMP1 depletion interfered with the externalization of PANX1.…”
Section: Discussionmentioning
confidence: 89%
“…17 Another aspect is the blebbing of apoptotic cells, implying an increase in the membrane surface area provided from the cell's internal membrane stores, such as the ER. In support of this notion, Franz et al 18 showed that apoptotic cells during cellular shrinkage expose calnexin, an ER integral membrane protein. Interestingly, the ER of phagocytes also supplies additional membrane required for phagocytosis, 19 indicating a possible homotypic interaction between surfaces of dying cells and phagocytes.…”
Section: Positive Regulators Of Uptake Dying Cellmentioning
confidence: 92%
“…Unlike DmCaBP1, these proteins seemed to directly move from the ER to the cell surface without being released from cells. Franz et al (33) showed that several ER-residing proteins, which were not analyzed in this study, are exposed at the surface of apoptotic cells. Therefore, the externalization or surface exposure of ER proteins could be a general feature in apoptotic cells, although the mechanism of relocation may vary from protein to protein.…”
Section: Discussionmentioning
confidence: 99%